O DESENVOLVIMENTO DA PROFISSIONALIDADE DOCENTE EM PROCESSOS DE IMERSÃO NO CONTEXTO DO PROGRAMA DE RESIDÊNCIA PEDAGÓGICA DA CAPES NA UFES - Bittencourt, Dalira da Fonseca (2022)
Understanding the process of developing the teaching professionalism of Residents immersed in the PRP/CAPES context of UFES – Campus Goiabeiras/Vitória was the primary objective of this study. The PRP is one of the actions that integrate the National Policy for Teacher Training, since 2018, under the articulation of CAPES. The study took place in an announcement perspective, in order to highlight the knowledge/advice/lessons from the experiences that, possibly, will contribute to the process of professionalization and development of the teaching professionalism of future teachers, because, the expectation is that the Residents, in addition to being subjects of stimulation and punctual experience, are especially subjects of experience. Narrative was used as a research methodology and data collection and analysis procedures. Although the investigation does not intend to deepen the analysis of the PRP/CAPES, indications were identified that the development of the Residents` teaching professionalism is composed of experiences of/in the process of immersion in basic education schools made possible by the Program, so that knowledge/advice/lessons from experience were evidenced. In the desired understanding, primarily, the study concluded that there were contributions from/in the process of immersion of Residents in the context of PRP/CAPES at UFES – Campus Goiabeiras/Vitória for the development of teaching professionalism, such as: i) expansion of training experiences in the practical- critical-reflective dimension; ii) opportunity to identify learning situations in practices of subversion to the established; iii) greater security in entering the profession; iv) expansion of ethical-affective relationships with colleagues in the profession and with children/students; v) exchange of knowledge with the school community; vi) possibility of reflection in action and on action and; vi) expansion of the ability to deal with the emotions and unpredictability of teaching.